2013
DOI: 10.1136/bjsports-2013-092380
|View full text |Cite
|
Sign up to set email alerts
|

Sports injuries and illnesses during the London Summer Olympic Games 2012

Abstract: BackgroundThe Olympic Movement Medical Code encourages all stakeholders to ensure that sport is practised without danger to the health of the athletes. Systematic surveillance of injuries and illnesses is the foundation for developing preventive measures in sport.AimTo analyse the injuries and illnesses that occurred during the Games of the XXX Olympiad, held in London in 2012.MethodsWe recorded the daily occurrence (or non-occurrence) of injuries and illnesses (1) through the reporting of all National Olympic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
675
8
26

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 610 publications
(763 citation statements)
references
References 40 publications
30
675
8
26
Order By: Relevance
“…The present study was initiated to identify the secondary traumatisms with the In comparison, taekwondo had the highest injury frequency with 39.1% during the London Games while in archery, canoe slalom and sprint, track cycling, rowing, shooting and equestrian sport less than 5% of athletes were injured (Engebresten, Soligard, Steffen et al, 2013). Our frequency of injuries in taekwondo, equal to 17.2%, is significantly higher (p = 0.032).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study was initiated to identify the secondary traumatisms with the In comparison, taekwondo had the highest injury frequency with 39.1% during the London Games while in archery, canoe slalom and sprint, track cycling, rowing, shooting and equestrian sport less than 5% of athletes were injured (Engebresten, Soligard, Steffen et al, 2013). Our frequency of injuries in taekwondo, equal to 17.2%, is significantly higher (p = 0.032).…”
Section: Discussionmentioning
confidence: 99%
“…Our frequency of injuries in taekwondo, equal to 17.2%, is significantly higher (p = 0.032). Compared with other Olympic combat sports, judo time loss injury frequency of 6% -9% during the last two SOGs was clearly lower than in taekwondo (16% -18%) but slightly higher than in boxing (4% -8%) and wrestling (5% -6%), respectively (Junge, Engebretsen, Mountjoy et al, 2009;Engebresten, Soligard, Steffen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…London 2012 Olympics is an excellent indicator of injury prevalence in contemporary elite sport. In a study of 2012 Olympic games, 10,568 athletes were monitored over the 17 day period and it was found that there where 1361 injuries (11% of athletes had at least one injury) (Engebretsen et al, 2013). In the same study, there were 24 fractures and some 35% of injuries resulted in prevention of competition or training.…”
Section: Exercise Demands Medicinementioning
confidence: 99%
“…This popularity also enjoys an equal distribution between the men's and women's game, which unfortunately is still rarely seen in other sports. These changes have also influenced the physiologic aspects of the game as well as the injury profile in the sport, which emerged as one of the most injury-prone ball sports [4,5]. The growing need for an appropriate scientific and medical envelope to support the game became evident; however, these aspects lagged behind those provided for other popular ball sports such as football, basketball, and rugby, a fact portrayed quite distinctively in the much lower number of scientific studies and English-language scientific publications in handball compared to these other sports.…”
Section: Introductionmentioning
confidence: 99%